Metastatic Malignant Ovarian Steroid Cell Tumor: A Case Report and Review of the Literature - Jessica Lee; Veena S. John; Sharon X. Liang; Catherine A. D’Agostino; Andrew W. Menzin (Case Reports in Obstetrics and Gynecology)
We report a case of malignant ovarian steroid cell tumor not otherwise specified (NOS) in a 47-year-old female who presented with hirsutism, virilization, and amenorrhea. At the time of laparotomy, the tumor had already spread to the pelvic cul-de-sac. She underwent a total hysterectomy, bilateral salpingo-oophorectomy, and tumor resection with no residual disease. She received three cycles of bleomycin, etoposide, and cisplatin (BEP) and is now free of disease 24 months after surgery. Literature review of ovarian steroid cell tumors NOS including clinicopathological features and clinical management was performed.